2000
DOI: 10.1046/j.1462-2920.2000.00082.x
|View full text |Cite
|
Sign up to set email alerts
|

Modification of the aggregation behaviour of the environmental Ralstonia eutropha‐like strain AE815 is reflected by both surface hydrophobicity and amplified fragment length polymorphism (AFLP) patterns

Abstract: SummaryAfter inoculation of the plasmid-free non-aggregative Ralstonia eutropha-like strain AE815 in activated sludge, followed by reisolation on a selective medium, a mutant strain A3 was obtained, which was characterized by an autoaggregative behaviour. Strain A3 had also acquired an IncP1 plasmid, pLME1, co-aggregated with yeast cells when co-cultured, and stained better with Congo red than did the AE815 strain. Contact angle measurements showed that the mutant strain was considerably more hydrophobic than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2010
2010

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…The knowledge about the mechanisms of resistance to heavy metals and especially their regulation stimulated further work in microbial ecology [46–51] and in environmental biotechnology [52]. Industrial applications of metal‐resistant bacteria and their genes include the use of biosensors for monitoring the concentration of heavy metals in a variety of substrates and soils [53–58], the development of bioreactors to remove heavy metals from polluted effluents or soils [59,60], and bioaugmentation [61] and phytoremediation [62] (Y. Wang, W. Hai, J. Vander Leyden and M. Mergeay, unpublished).…”
Section: Introduction:ralstonia Metallidurans: General Description Amentioning
confidence: 99%
“…The knowledge about the mechanisms of resistance to heavy metals and especially their regulation stimulated further work in microbial ecology [46–51] and in environmental biotechnology [52]. Industrial applications of metal‐resistant bacteria and their genes include the use of biosensors for monitoring the concentration of heavy metals in a variety of substrates and soils [53–58], the development of bioreactors to remove heavy metals from polluted effluents or soils [59,60], and bioaugmentation [61] and phytoremediation [62] (Y. Wang, W. Hai, J. Vander Leyden and M. Mergeay, unpublished).…”
Section: Introduction:ralstonia Metallidurans: General Description Amentioning
confidence: 99%
“…Pseudomonas putida CP1 exhibits auto-aggregation during the degradation of monochlorophenols and phenol, and it has been shown that this is a response to the toxicity of the added substrates (Farrell & Quilty, 2002). Bossier et al (2000) observed that after inoculation of the non-aggregative Ralstonia eutropha-like strain AE815 into activated sludge, reisolation on selective medium yielded mutant strain A3, which was characterized by autoaggregative behaviour.…”
Section: Introductionmentioning
confidence: 99%